The experience of subaortic obstruction repair concomitantly with total cavopulmonary connection - Bairamov, E.; Poznyak, Y.; Stogova, O.; Romanyuk, O. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Systemic ventricle outflow obstruction (SVOTO) could result in unfavorable hemodynamic conditions that might worsen the prognosis of patients with total cavopulmonary connection (TCPC). From 2005 to 2015, 92 consecutive children with variable single ventricle pathologies underwent TCPC procedure, 10,8% (n=10) of which was presented with SVOTO. We used two main options for surgical relief of SVOTO: the first consisted in ventricular septal defect enlargement, the second one – in modified Damus-Kaye-Stansel procedure (DKS). There was 1 (1,2%) early death in the control group and no mortality in study groups through the study period. Two patients in study groups underwent a permanent pacemaker implantation. SVOT gradient decreased from 17±5,82 mm Hg preoperatively to 8±4,33 mm Hg after the procedure. Our results indicate that the SVOTO relief at the moment of TCPC does not cause significant increase in morbidity and mortality in the early postoperative period. The results suggest that the DKS is the method of choice with regard to avoidance of heart block or adequate removal of SVOTO.